THE MEDIATING ROLE OF PSYCHOLOGICAL EMPOWERMENT AND CREATIVE PROCESS ENGAGEMENT ON THE INFLUENCE OF LEADERSHIP EMPOWERMENT AND CREATIVITY: CASE STUDY OF CPNS LECTURE’S - Andi Tenri Pada; Andi Wahyudin (SEAN Institute, 2023)
This study aims at testing the influence of empowering leadership on the creativity of CPNS Lecturers, by exploring the mediating variables, namely psychological empowerment and creative process engagement. The research was conducted at CPNS Lecturers who had participated in the 2021-2022 LATSAR program at the Center for Training and Development and Government Management Studies, LAN RI, Makassar City. The hypothesis testing uses Structural Equation Modeling (SEM). The research findings show that empowering leadership has a positive influence on the psychological empowerment of lecturers' CPNS, where this interaction also affects the engagement of the creative process. The attachment to the creative process then has a positive effect on creativity.